1997
DOI: 10.1002/(sici)1096-9136(199704)14:4<284::aid-dia348>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

NO-dependent Smooth Muscle Vasodilatation is Reduced in NIDDM Patients with Peripheral Sensory Neuropathy

Abstract: In order to determine the involvement of denervation in endothelium‐independent, nitric oxide (NO)‐dependent smooth muscle vasodilatation, we have measured vascular endothelial and smooth muscle function in three groups of age‐ and sex‐matched patients: 8 patients with non‐insulin‐dependent (Type 2) diabetes mellitus (NIDDM) with neuropathy; 7 NIDDM patients without neuropathy; and 10 non‐diabetic control subjects. Laser Doppler probes were used to measure blood flow in the dorsum of the left foot. Vascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…Recent data suggest that impaired nitric oxide (NO) synthesis plays an important role in the pathogenesis of painful diabetic neuropathy. Sasaki et al (5) and Rodella et al (6) demonstrated that impaired neuronal NO generation in diabetic rats induced hyperalgesia, whereas Pitei et al (7) showed that decreased NO production contributed to a reduction in endoneurial blood flow in type 2 diabetic patients with peripheral sensory neuropathy. The preservation of endothelialdependent vasodilatory responses to nitroglycerin (8), which directly releases NO, further implicates a defect or defects in endoneurial NO synthesis as the cause of impaired vascular responses in diabetes.…”
mentioning
confidence: 99%
“…Recent data suggest that impaired nitric oxide (NO) synthesis plays an important role in the pathogenesis of painful diabetic neuropathy. Sasaki et al (5) and Rodella et al (6) demonstrated that impaired neuronal NO generation in diabetic rats induced hyperalgesia, whereas Pitei et al (7) showed that decreased NO production contributed to a reduction in endoneurial blood flow in type 2 diabetic patients with peripheral sensory neuropathy. The preservation of endothelialdependent vasodilatory responses to nitroglycerin (8), which directly releases NO, further implicates a defect or defects in endoneurial NO synthesis as the cause of impaired vascular responses in diabetes.…”
mentioning
confidence: 99%
“…Different investigators (Sasaki et al, 1998;Rodella et al, 2000) have demonstrated that impaired NO generation in diabetic rats results in hyperalgesia, and that the administration of L-arginine, known to enhance the circulating NO concentration, is antinociceptive in diabetic mice. Pitei et al (1997) showed that decreased NO production contributes to reduced endoneuronal blood flow in diabetic patients and causes pain, whereas the local application of NO donors such as isosorbide dinitrate (Yuen et al, 2002) or nitroglycerin (Francis et al, 1977;Agrawal et al, 2007) relieves pain and burning sensations in patients with PDN.…”
Section: Introductionmentioning
confidence: 95%
“…The pathophysiology of PDN remains unclear, but neurogenic and vascular components have been described (Yorek, 2003). For instance, peripheral demyelination, reduction in nerve conductance, and progressive degeneration of peripheral sensory fibers (Watkins, 1984) along with microvascular and macrovascular abnormalities dependent on dysfunctional endothelium, the innermost layer of the blood vessel, have long been established in experimental animal models and in diabetic patients (Pieper and Gross, 1988;Pitei et al, 1997) as well as in individuals who will later develop diabetes (Cosentino and Luscher, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired or reduced endoneurial nitric oxide synthethase has been implicated in the pathogenesis of painful neuropathies such as those found in diabetes [52]. Yuen and colleagues [53] have demonstrated a 50% reduction of painful burning sensations recalcitrant to other therapies in a small, well-controlled study.…”
Section: Isosorbide Dinitrate Spray (Isocard)mentioning
confidence: 99%